PELATIHAN DAN PENDAMPINGAN PENGOLAHAN NUGGET LELE WORTEL PADA KELOMPOK WANITA TANI DI DUSUN GRENJENG, DESA GANDUSARI, KECAMATAN BANDONGAN, KABUPATEN MAGELANG - Sari, Annisa Novita (Fakultas Pertanian_Universitas Tidar, 2023)
Catfish is a type of freshwater fish that contains abundant protein. Catfish is also a food source with high nutrition so it needs to be processed properly in order to increase people's interest in consuming catfish. One of them is by processing catfish into nuggets, by combining animal food and vegetable food, so that this food will have a nutritional content that is high enough to be consumed. The method used is the lecture method and active participation in the training activities provided. The training was attended by the Head of Gandusari Village, Head of farmer women's group (KWT) Permai Tani. The activity started with preparing tools and materials, delivering material about digital marketing, practicing making carrot catfish nuggets, and handing over cooking equipment to KWT Permai Tani. From this activity it can be concluded that the public likes the Carrot Catfish Nugget products that have been made. The suggestion for the next activity is that the community can independently practice directly making fishery products.